The causality between gut microbiome and anorexia nervosa: a Mendelian randomization analysis - Xia, Xuan; He, Shu-yang; Zhang, Xiao-Lin; Wang, Decheng; He, Qian; Xiao, Qing-Ao; Yang, Yong (Frontiers in Microbiology, 2023)
Background and aim Nutrient production by intestinal microbiota corresponds to regulate appetite while gut microbial composition was influenced by diet ingestion. However, the causal relationship between gut microbial taxa and anorexia nervosa (AN) remains unclear. Mendelian Randomization (MR) is a novel research method that effectively eliminates the interference of confounding factors and allows for the exploration of the direct causal effects between exposure and outcome. This study employs MR to explore the causal effect between AN and specific gut microbiome. Methods Large-scale Genome Wide Association Study (GWAS) data of AN and 211 gut microbes were obtained from the IEU open GWAS project and Mibiogen Consortium. Two-sample MR was performed to determine the causal relationship between gut microbiota and AN. Furthermore, a bi-directional MR analysis was to examine the direction of the causal relations. The Bonferroni correction test was used to adjust potential correlations among microbial taxa. Result In forward MR analysis, 10specific gut microbial taxa have an impact on the occurrence of AN (the p value of IVW <0.05). The high abundance of Genus Eubacteriumnodatumgroup ID: 11297 (OR:0.78, 95% CI:0.62–0.98, p = 0.035) and Class Melainabacteria ID: 1589 (OR:0.72, 95% CI:0.51–0.99, p = 0.045) may be considered protective factors for AN. But after Bonferroni correction, only Class Actinobacteria ID:419 (OR:1.53, 95% CI:1.19–1.96, p = 0.00089) remained significantly associated and high abundance of Class Actinobacteria ID:419 considered as a risk factor for AN. In the reverse MR analysis, AN influences 8 gut microbial taxa with none-statistically significant associations after adjustment. Conclusion We identified a significant correlation between AN and 18 microbial taxa which have not been previously reported. Among them, 10 kinds of gut bacteria may affect the occurrence of AN, and the status of AN would affect 8 kinds of gut bacteria. After correction, the Class Actinobacteria ID:419 continued to exert an influence on AN.